Tracking control for a flat system under disturbances: a fixed-wing UAV example. Issue 16 (2022) - Do, Huu Thinh; Nicolau, Florentina; Stoican, Florin; Prodan, Ionela
Abstract: This paper considers a class of systems admitting several flat representations and proposes a trajectory tracking controller design which accounts for disturbance rejection. Set invariance is used for characterizing the tracking and estimation error dynamics. Furthermore, some insights on the disturbance propagation in case of different flat representations for a fixed-wing Unmanned Aerial Vehicle (UAV) system are highlighted via simulations and comparisons.